Pelatihan Pengolahan Produk Berbasis Nanas Melalui Pemberdayaan Wanita Desa Margoluwih Kabupaten Sleman - Ismiasih, Ismiasih; Trimerani, Resna; Handru, Alan; Honin , Eunike Sindri; Fadillah , Yoeva Wardha (Madani : Indonesian Journal of Civil Society, 2025)
The community in Margoluwih Village is currently developing pineapple cultivation. While pineapple marketing is still limited to fresh form when the harvest season comes, pineapple production will be abundant so that prices can fall. Therefore, there needs to be a follow-up to overcome this by making other derivative products such as pineapple jam and syrup. The Community Partnership Empowerment Program (PKM), has provided a positive perception to partners regarding the diversification of pineapple processing into products with economic value, and as a solution to overcome the peak harvest in addition to increasing competitiveness and capturing market opportunities. The products offered from pineapple processing received a good response from partners, namely through pineapple syrup and jam processing. The PKM program was carried out through several stages starting from preliminary surveys, socialization, counseling, and training. The PKM method used during the activity was Participatory Rural Appraisal (PRA). This technique involves the active role of all partners in the activity. The PKM program succeeded in increasing the knowledge, skills, and abilities of partners in processing pineapple into products with economic value as a whole by 97%. In addition, PKM activities have had positive impacts on partners, especially in utilizing free time for productive activities that can generate income and economic resources for families.